A formula for creation and its applications to generate plots on computers - Hai, Doan Nguyen (Journal of Computer Science and Cybernetics, 2016)
In this paper we propose a formula for creation and present the design of a plot generation system as one application of this formula. Such a system has been implemented in our university in 1993.